ANTARA KEUTAMAAN DAN KEPANTASAN ADAM SMITH DAN FILSAFAT STOA - Wattimena, Reza A. A. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2007)
Adam Smith's position as a philosopher of Ethics has been consigned to oblivion due to his more popular thoughts on Economics. This article is an attempt to revisit the ethical side of his thought based on his book The Theory of Moral Sentiment. In this book, Smith made sharp distinction between virtue as morality for noble view, and propriety as moral quality forcommon people. Smith used the concepts of 'virtue' and 'propriety' to analyze human moral behaviour. We can trace this conceptual distinction back to an ancient Greek philosophical school, namely the Stoic Philosophy. This paper will describe the influence of the Stoic Philosophy to Adam Smith MoralPhilosophy.